Older Adults’ Use of Extended Reality: A Systematic Review - Margrett, Jennifer A.; Ouverson, Kaitlyn M.; Gilbert, Stephen B.; Phillips, L. Alison; Charness, Neil (Frontiers in Virtual Reality, 2022)
Research has pointed to the potential of extended reality (XR), including virtual, mixed, and augmented reality, for broadly impactful benefits, including learning, physical activity and health, and psychosocial aspects such as increased empathy and reduced loneliness. More research is needed to evaluate the outcomes of XR in new populations of users, including older adults. The purpose of this systematic review is to summarize the extant literature that centers on older adult use of XR in order to identify key themes, as well as identified benefits and barriers to XR use. In total, 17 studies from 2015-2019 met the inclusion criteria, namely that the study collected data from a sample of adults at least 60 years of age interacting with a 3D virtual environment. Through qualitative analysis of the corpus, six thematic areas were identified: Socialization, Physical Rehabilitation, Driving Simulation, Cognitive Training, Reminiscence, and Assessment. Furthermore, the unique contexts and outcomes of XR use, preferences for XR use, and reported occurrences of cybersickness in older adults are highlighted. Research after 2019 is also noted. This review is intended to guide future research supporting deployment of XR with older adults, emphasizing the psychosocial impacts of the technology.